Investigation on the Influences of Curing Time on the Cracking Resistance of Semiflexible Pavement Mixture - Hua Tan; Zijia Xiong; Minghui Gong; Jie Chen; Jinxiang Hong (Advances in Materials Science and Engineering)
Semiflexible pavement (SFP) is constructed by pouring grouting material into porous asphalt (PA) mixture. SFP has been widely used to address the rutting distress issues across China in recent years. However, studies on its cracking resistance are limited and the failure mechanism of the SFP mixture has not been fully explored nor understood in a comprehensive way. Moreover, the influences of the curing time on the cracking property of the SFP mixture are still not clear. To this end, the strength development and shrinkage properties of grouting materials are determined by utilizing the three-point beam bending test and the shrinkage test. The semicircular bending (SCB) test and the scanning electron microscope-energy-dispersive spectrum (SEM-EDS) are conducted in this study to investigate the cracking resistance and failure mechanism of SFP mixtures with different curing days. Results show that both the strength and shrinkage of grouting materials would develop as the curing time was extended from 0 days to 14 days. SCB test results show that SFP mixtures have higher tensile strength but a lower flexibility index (FI) than PA mixture. It is found that the cracking resistance of SFP mixture is influenced by both the grouting materials’ strength and shrinkage. SEM-EDS analysis demonstrates that the cement-asphalt interface is a stress concentration site and therefore is the weak zone where cracks would initially develop. The microcracks found in the interface zone with different curing days may contribute to the decline of the SFP mixture’s anticracking ability. This study sheds light on the further application of SFP in practical projects.